2008
DOI: 10.1177/0265407507086806
|View full text |Cite
|
Sign up to set email alerts
|

Relationship social comparison tendencies, insecurity, and perceived relationship quality

Abstract: Three studies examine associations between relationship social comparison (RSC) tendencies, insecurity, and perceived relationship quality. Study 1 (68 females, 9 males) showed that RSC was associated with self-esteem, anxious and avoidant attachment styles, and relationship insecurity. RSC associations with anxious attachment and insecurity, but not avoidant attachment, held when controlling for self-esteem. Study 2 (322 females, 95 males) showed that RSC was associated with intimacy, satisfaction, investment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 19 publications
0
18
0
1
Order By: Relevance
“…Social comparisons are common within both the close relationship literature (e.g., Broemer & Diehl, ; Buunk et al, ; Buunk & Ybema, ; Smith LeBeau & Buckingham, ) and the nonrelationship literature (e.g., Bui & Pelham, ; Lockwood, ). Of interest to the present research, previous researchers have suggested that how an individual interprets a social comparison may have implications for the self and one's relationship (e.g., Buunk et al, ; Van der Zee et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Social comparisons are common within both the close relationship literature (e.g., Broemer & Diehl, ; Buunk et al, ; Buunk & Ybema, ; Smith LeBeau & Buckingham, ) and the nonrelationship literature (e.g., Bui & Pelham, ; Lockwood, ). Of interest to the present research, previous researchers have suggested that how an individual interprets a social comparison may have implications for the self and one's relationship (e.g., Buunk et al, ; Van der Zee et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Secure individuals hold more positive beliefs (Collins & Read, ) and expectations (Baldwin, Fehr, Keedian, Seidel, & Thomson, ) about others and explain their partner's behavior in more positive terms (N. L. Collins, 1996) than insecure individuals. Insecurity is also related to greater social comparison tendencies (Smith LeBeau & Buckingham, ). Therefore, insecure relative to secure individuals should make more relationship social comparisons and more negative interpretations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations